Prevalence of asthma and other allergic conditions in Colombia 2009–2010: a cross-sectional study (2012)
Background While it is suggested that the prevalence of asthma in developed countries may have stabilized, this is not clear in currently developing countries. Current available information for both adults and children simultaneously on the burden and impact of allergic conditions in Colombia and in many Latin American countries is limited. The objectives of this study were to estimate the prevalence for asthma, allergic rhinitis (AR), atopic eczema (AE), and atopy in six colombian cities; to quantify costs to the patient and her/his family; and to determine levels of Immunoglobulin E (IgE) in asthmatic and healthy subjects. Methods We conducted a cross-sectional, population-based study in six cities during the academic year 2009–2010. We used a school-based design for subjects between 5–17 years old. We carried out a community-based strategy for subjects between 1–4 years old and adults between 18–59 years old. Serum samples for total and antigen-specific (IgE) levels were collected using a population-based, nested, case–control design. Results We obtained information on 5978 subjects. The largest sample of subjects was collected in Bogotá (2392). The current prevalence of asthma symptoms was 12% (95% CI, 10.5-13.7), with 43% (95% CI, 36.3-49.2) reporting having required an emergency department visit or hospitalization in the past 12 months. Physician diagnosed asthma was 7% (95% CI, 6.1-8.0). The current prevalence of AR symptoms was 32% (95% CI, 29.5-33.9), and of AE symptoms was 14% (95% CI, 12.5-15.3). We collected blood samples from 855 subjects; 60.2% of asthmatics and 40.6% of controls could be classified as atopic.